Sexual function, depression, and quality of life in patients with irritable bowel syndrome - Keshavarzi, Amir; Talebi, Seyed Saman; Ahmadpanah, Mohammad; Soltanian, Alireza; Torkashvand, Saman (BMC gastroenterology, 2025)
Background Irritable bowel syndrome (IBS) is a prevalent functional disorder of the gastrointestinal (GI) tract, often accompanied by depression and sexual dysfunction. Depression and IBS may share similar pathophysiological mechanisms, making it essential to understand them for effective treatment. This study aims to compare the state of sexual function, depression, and quality of life in IBS patients experiencing depression with that of healthy subjects. Methods In this cross-sectional study, three groups of 49 individuals each were included: patients with irritable bowel syndrome (IBS), patients with depression without symptoms of IBS, and healthy individuals attending university internal clinics in Hamedan city. All patients were sexually active. Quality of life was assessed using the World Health Organization Quality of Life-BREF (WHOQOL-BREF) questionnaire, depression severity was measured using the Beck Depression Inventory (BDI), female sexual function was evaluated using the Female Sexual Function Index (FSFI), and male sexual function was assessed using the Male Sexual Health Questionnaire (MSHQ). Data were analyzed using the Chi-square test and analysis of variance. Results The study compared depression scores, quality of life, and sexual performance among three groups: irritable bowel syndrome (IBS) patients, patients with depression, and a control group. Results showed that depression scores were significantly higher in the IBS and depression groups compared to the control group. Quality of life scores did not significantly differ between IBS and depression groups but were lower in both compared to the control group. Sexual performance, both in men and women, differed significantly across all groups. The relationship between quality of life and depression in IBS patients was inverse ( r =-0.71, P = 0.001), while depression negatively correlated with sexual performance in men ( r =-0.550, P = 0.001). Conversely, higher quality of life and better sexual performance showed a positive relationship in men ( r = 0.335, P < 0.001). Based on the findings of the current study, it could be said that depression is significantly higher in IBS patients and depression is not the only intervening factor in the low sexual quality of IBS patients. Other factors such as physiological symptoms, medication side effects, and psychological stressors also contribute to causing sexual dysfunction in these IBS patients.